Understanding Postpartum Mothers’ Perspectives of Chrononutrition Approaches: A Qualitative Study - Elizabeth N. Davis; Zena A. Patel; Christie Kirchoff; Courtney M. Peterson; Gareth R. Dutton; Erin Contratto; Camille R. Schneider-Worthington (Journal of the Academy of Nutrition and Dietetics, 2026)

Habits at home: How the home food environment shapes caregivers’ eating habits - Demetria R. Pizano; Camille Schneider-Worthington; Sarah-Jeanne Salvy; Alanis Stansberry; Andrea L. Davis; Gareth R. Dutton (Appetite, 2026)

Beyond Perceived Discrimination: Weight Discrimination in College Social Networks Is Associated With Poorer Mental and Behavioral Health - Alena C. Borgatti; Andrea L. Davis; Gareth R. Dutton (Journal of the Academy of Nutrition and Dietetics, 2025)

Weighing the Evidence of Common Beliefs in Obesity Research - Krista Casazza; Andrew Brown; Arne Astrup; Fredrik Bertz; Charles Baum; Michelle Bohan Brown; John Dawson; Nefertiti Durant; Gareth Dutton; David A. Fields; Kevin R. Fontaine; Steven Heymsfield; et al. (Critical Reviews in Food Science and Nutrition, 2015)

Estimating the Value of Non‐Use Benefits from Small Changes in the Provision of Ecosystem Services - ADAM DUTTON; GARETH EDWARDS‐JONES; DAVID W. MACDONALD (Conservation Biology, 2010)
The unit of trade in ecosystem services is usually the use of a proportion of the parcels of land associated with a given service. Valuing small changes in the provision of an ecosystem service presents obstacles, particularly when the service provides non‐use benefits, as is the case with conservation of most plants and animals. Quantifying non‐use values requires stated‐preference valuations. Stated‐preference valuations can provide estimates of the public's willingness to pay for a broad conservation goal. Nevertheless, stated‐preference valuations can be expensive and do not produce consistent measures for varying levels of provision of a service. Additionally, the unit of trade, land use, is not always linearly related to the level of ecosystem services the land might provide. To overcome these obstacles, we developed a method to estimate the value of a marginal change in the provision of a non‐use ecosystem service—in this case conservation of plants or animals associated with a given land‐cover type. Our method serves as a tool for calculating transferable valuations of small changes in the provision of ecosystem services relative to the existing provision. Valuation is achieved through stated‐preference investigations, calculation of a unit value for a parcel of land, and the weighting of this parcel by its ability to provide the desired ecosystem service and its effect on the ability of the surrounding land parcels to provide the desired service. We used the water vole ( Arvicola terrestris ) as a case study to illustrate the method. The average present value of a meter of water vole habitat was estimated at UK£12, but the marginal value of a meter (based on our methods) could range between £0 and £40 or more .